Inteligência emocional das equipes no contexto de gestão de projetos - Goldberg, Renato (2024)
The context of work with greater pressure and companies searching for competitiveness requires increasingly qualified professionals. Although technical aspects related to professionals' skills are critical success factors, emotional aspects are increasingly seen as determining factors for problem- solving, delivering better results, improving interaction between team members, among others. in addition to these aspects linked to emotional skills in the pursuit of competitiveness, the projectization of organizations and the adoption of new project management practices to deal with the context of constant change and uncertainty can also be evidenced. That said, the importance of emotional intelligence is increasingly seen as one of the success factors, not only in personal life, but of great relevance in professional life. Emotional intelligence is interconnected with several aspects such as career choice, interpersonal relationships in daily work, conflict resolution, listening skills and knowing how to make oneself understood correctly and obtaining the expected result. in addition, there is much research on professionals who deviate from their routines due to stress and lack of quality of life. Based on this scenario, this dissertation aims to present a model to develop emotional intelligence in teams to assist professionals involved in projects. Regarding the methodological procedures, a strategy was applied through questionnaires and interviews, allowing a qualitative and quantitative analysis. This was done in two stages, namely: (i) development of the research; (ii) validation of the conceptual model through the application of training, which was understood as an enabling element for the development of emotional intelligence in teams. The first part of the research started with the execution of a systematic literature review to understand theoretical assumptions and research gaps on the use of emotional intelligence in project teams, which was carried out to enable the construction of the conceptual model developed and its validation. in the second stage of this research, questionnaires and semi-structured interviews were applied. To this end, an intervention process based on structured training of emotional intelligence in teams in a multinational project- oriented company was applied. The training in emotional intelligence of teams involved 45 employees from different sectors of a project-oriented company, which lasted 32 hours divided into 8 meetings, highlighting its influence on communication, trust and conflict mitigation. The contributions of this research can be evidenced in the prescription of activities to develop the emotional intelligence of project teams, as well as in the proposal of a model that identifies the factors that explain the relationship between the use of emotional intelligence of teams among project professionals. The theoretical contribution of this research enriches the literature on emotional intelligence of teams by highlighting its importance in collaborative contexts. The study reinforces the idea that emotional intelligence of teams is a critical success factor, capable of generating significant benefits in organizations. The study offers guidelines to reduce the negative impacts of conflicts and improve collaboration among team members. The practical contribution of this study goes beyond the individual development of emotional skills. It proposes a comprehensive model that aims to improve dynamics in the context of projects, positively influencing the work environment by identifying dimensions and practices that promote an emotionally healthy environment, highlighting their influence on communication, trust building and conflict mitigation. this research is aligned with research line 2 (project management) linked to the postgraduate program in project management – PPGP UNINOVE. This dissertation proposal is also aligned with other research by its advisor linked to the project axis “people management and project management”.